Nondegradative Extraction and Measurement of Uric Acid from Poultry Litter. Issue 4 (17th May 2013) - Mowrer, Jake; Kissel, David E.; Cabrera, Miguel; Hassan, Sayed M.
Abstract : Due to limited solubility of uric acid from poultry litter (PL), alkaline solutions are frequently used to extract uric acid from PL for measurement, but the high pH can cause oxidation of the analyte. Our objective was to compare 0.1 M sodium acetate, 0.025 M Li2 CO3, and a NaOH/Na2 PO4 buffer as a means of extracting uric acid from PL for analysis by high‐pressure liquid chromatography (HPLC). In laboratory experiments, extractant‐induced degradation of reagent uric acid proceeded at a rate of 80 g kg −1 d −1 in 0.025 M of Li2 CO3 (pH 11.2) and a NaOH/Na2 PO4 buffer (pH 12.4) compared with no degradation in sodium acetate over a 2‐d period. In extracted PL samples, the alkaline extractants were found to enhance the enzymatic oxidation of uric acid to completion in Li2 CO3 and by 800 g kg −1 in a NaOH/Na2 PO4 buffer over the same 2‐d period. Sodium acetate extraction resulted in minimal loss of analyte (30 g kg −1 ), possibly due to thermal inactivation of the responsible enzyme uricase. Stabilization of the dissolved uric acid extracted from PL samples allowed for the development of a very accurate measurement procedure by HPLC with ultraviolet (UV)–visible light spectrometer (VIS) detection at 290 nm. Our results suggest a reporting limit of 8.5 mg uric acid–N kg −1 of litter. Of the 118 PL samples that were analyzed in this study, uric acid‐, ammonium‐, and nitrate‐N concentrations accounted for an average of 9.4, 17.4, and 1.2%, respectively, of the total N present in PL.